2012
DOI: 10.1143/jjap.51.03cb04
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Leakage Current of Thin-Film Transistors with ZnO Channels Formed at Various Oxygen Partial Pressures under Visible Light Irradiation

Abstract: The effects of the oxygen partial pressure [p(O2)] during ZnO sputtering on the photo-leakage current of a ZnO thin-film transistor (TFT) were investigated. The photo-leakage current increased with decreasing p(O2). When the photon energy of incident light is smaller than the band-gap of the ZnO, electrons are excited from the trapped states existing near the valence band. It was found that the density of the electron traps increased when the p(O2) decreased. Moreover, the trap states were formed at ∼0.5 eV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…When the T ITZO was further thickened to 75 and 100 nm, the photon energy of excited OFF-current gradually reduced to 2.48 and 2.34 eV, respectively. These phenomena can be interpreted as follows: for the channel layer with T ITZO of 25 and 45 nm, the high-density defect states occupy the valence band maximum ( E V ), which is ~2.70 eV away from the conduction band ( E C ), similar to the results of a-IGZO devices [ 24 ]. In terms of the T ITZO at 75 and 100 nm, given the long deposition duration in the sputtering chamber, the ITZO films suffer from strong plasma bombardment.…”
Section: Resultssupporting
confidence: 54%
“…When the T ITZO was further thickened to 75 and 100 nm, the photon energy of excited OFF-current gradually reduced to 2.48 and 2.34 eV, respectively. These phenomena can be interpreted as follows: for the channel layer with T ITZO of 25 and 45 nm, the high-density defect states occupy the valence band maximum ( E V ), which is ~2.70 eV away from the conduction band ( E C ), similar to the results of a-IGZO devices [ 24 ]. In terms of the T ITZO at 75 and 100 nm, given the long deposition duration in the sputtering chamber, the ITZO films suffer from strong plasma bombardment.…”
Section: Resultssupporting
confidence: 54%
“…[6][7][8] We have already reported that the photo leakage current increases with decreasing oxygen partial pressure [p(O 2 )] during the sputter deposition of ZnO films and that even when the photon energy of the incident light is smaller than the band gap of ZnO, electrons are excited from the trapped states existing near the valence band (E V ). 9) In addition, we reported that the density of electron traps increases when p(O 2 ) decreases. Trapped states are formed at $0:5 and 2.8-3.2 eV from the conduction band (E C ) as p(O 2 ) decreases.…”
mentioning
confidence: 94%
“…Although the optical band gap of the ZnO TFT was reported to be 3.28 eV. 9) The photo leakage current began to increase when the photon energy exceeded 2.7 eV. The photo leakage current then increases with increasing photon energy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1) We found that there was photo-induced leakage current under visible light irradiation for oxide TFTs even the band gap of oxide semiconductor was larger than the photon energy of visible light. 2) It is because large amounts of trap states related to oxygen vacancies (V O ) located within a band gap of oxide semiconductor.…”
Section: Introductionmentioning
confidence: 99%